Increase Community Income In the village Putat Jaya Through Batik Gardens - Wiwik Handayani (LPPM of NAROTAMA UNIVERSITY, 2018)
Dolly is part of the Putat Jaya urban village which is a prostitution localization and is given kebun jeruk. Kebun Jeruk that has negative connotation. Based on these concerns, the researchers came up with an idea to change the image of the region. The change of image from the term kebun jeruk will be kebun batik. One of the efforts that will be done in community service in the Dolly region is to provide batik skills. Provision of training is done gradually begins with the manufacture of batik dipup followed by batik and batik naturally. Batik training aims to achieve the creation of image area in accordance with the goal to be achieved that is the image image kebun jeruk into kebun batik. If people in the Dolly area are able to make batik, then there will be many batik sales so that the image of the area will change, just like the village of batik. The change of image or image will lift the good name of the region, the community as well as provide income to the community in a good way. The results of the monitoring showed that the training was fruitful because there was a continuity of activity that is still the residents who continue to make batik, and even the result of the show was displayed in the store of various SME products in DS Store (Dolly Saiki Point) to be sold.